Helicobacter pylori Infection and Iron-Deficiency Anemia: Mechanisms, Clinical Evidence, and Therapeutic Implications: English - Alza Hamonangan Pasaribu; Wirandi dalimunthe (Argael Publisher, an imprint of CV. ARGA FARMA, 2026)
Iron-deficiency anemia (IDA) is common, but its persistence cannot always be explained by diet, physiological demand, blood loss, or recognized malabsorption. Helicobacter pylori infection has therefore been investigated as a potentially modifiable contributor to disturbed iron homeostasis. To critically synthesize recent evidence on the association between H. pylori infection and iron deficiency (ID)/IDA, the biological mechanisms involved, and the implications for testing and eradication. A structured narrative search of PubMed, Google Scholar, ScienceDirect, Frontiers, and publisher websites was updated through 18 June 2026. Six core human studies with direct iron or hematological outcomes were comparatively appraised, while systematic reviews, mechanistic literature, and international guidelines were used for contextual interpretation. The evidence is population-dependent rather than uniformly consistent. In non-elderly adults, infection was associated with ID (adjusted odds ratio [OR] 3.03) but not clearly with anemia or IDA. A large sex-stratified study reported an association with ID/IDA in women. Pediatric meta-analyses found increased odds of ID (OR 1.52) and IDA (OR 1.83), although one analysis found no significant association with anemia as a broad endpoint and reported substantial heterogeneity. A longitudinal birth cohort suggested a strong association between CagA-positive strains and IDA, whereas a seven-patient adolescent case series documented sustained hematological improvement after successful eradication. The most plausible pathways are impaired gastric iron handling and inflammation-mediated hepcidin upregulation; bacterial iron acquisition and microscopic blood loss remain biologically credible but less directly quantified. H. pylori should be regarded as a possible contributor, not a universal cause, of IDA. Testing is most defensible in unexplained or iron-refractory IDA after common causes have been evaluated. Pediatric testing should follow endoscopy-based guideline indications rather than routine non-invasive screening.